2015
DOI: 10.1002/2014jd022941
|View full text |Cite
|
Sign up to set email alerts
|

Simulated warm periods of climate over China during the last two millennia: The Sui‐Tang warm period versus the Song‐Yuan warm period

Abstract: A 2000 year simulation forced by the external forcings of the last two millennia is carried out with the Community Earth System Model. We compare climate changes over China between the peak Sui-Tang warm period (Sui-TangWP; 650-700 A.D.) and Song-Yuan warm period (Song-YuanWP; 950-1000 A.D.), which were two key culturally, economically, and educationally prosperous eras in Chinese history. The simulation indicates warm conditions in both periods, but the warmth is mainly seen in East China in the peak Sui-Tang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In particular, Man et al [] suggested a stronger EASM and a north‐flood and south‐drought pattern over eastern China during the MCA based on Max‐Planck‐Institut (MPI) model results, whereas precipitation is enhanced (suppressed) in summer over the whole of eastern China in ECHO‐G simulations [ Liu et al , ]. However, Yan et al [] found drier conditions in North China from 950 to 1000 A.D. in a Community Earth System Model model simulation. In addition, based on Community Climate System Model version 2.0 (CCSM2.0) model results, Peng et al [] indicated that several severe droughts had occurred over eastern China in the past millennium, which were associated with a weakened EASM.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Man et al [] suggested a stronger EASM and a north‐flood and south‐drought pattern over eastern China during the MCA based on Max‐Planck‐Institut (MPI) model results, whereas precipitation is enhanced (suppressed) in summer over the whole of eastern China in ECHO‐G simulations [ Liu et al , ]. However, Yan et al [] found drier conditions in North China from 950 to 1000 A.D. in a Community Earth System Model model simulation. In addition, based on Community Climate System Model version 2.0 (CCSM2.0) model results, Peng et al [] indicated that several severe droughts had occurred over eastern China in the past millennium, which were associated with a weakened EASM.…”
Section: Introductionmentioning
confidence: 99%
“…All individual simulations show warmer temperatures in the MCA and cooler in the LIA (Figure 4, with reference to the period of 1401–1850 AD), consistent with that of the reconstruction. The results agreed with previous studies based on the model simulations, which showed warmth conditions in the peak MCA (Yan et al ., 2015) and cold conditions in the LIA (Zhou et al ., 2019) over the whole of China. However, the performance differences are more remarkable for the simulations than the reconstruction over the MCA (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…North-south differences in the environment (northern drought and humid south) encouraged invaders from Mongolia to move toward southern China and compete for resources. Migration contributed to the population of Jiang Xi Province (Nan Chang County Annals) and lasted until the Yuan Dynasty (1271-1368 AD) when the southern China experienced a warm period (Yan et al, 2015). The warm and humid climate in the middle Yangtze River catchment encouraged population development.…”
Section: Possible Controlling Factorsmentioning
confidence: 99%